443 paediatric cases of malignant melanoma registered with the German Central Malignant Melanoma Registry between 1983 and 2011. Issue 7 (May 2015) - Brecht, Ines B.; Garbe, Claus; Gefeller, Olaf; Pfahlberg, Annette; Bauer, Jürgen; Eigentler, Thomas K.; Offenmueller, Sonja; Schneider, Dominik T.; Leiter, Ulrike
Abstract Background Malignant melanoma is a very rare paediatric tumour. This study was performed in order to understand clinical features and prognosis of malignant melanoma in children and adolescents. Methods 443 patients ⩽18 years of age with malignant melanoma were prospectively registered with the German Central Malignant Melanoma Registry between 1983 and 2011. Cases were collected from 58 participating centres. 276 paediatric cases with a follow-up >3 months were evaluated for survival probabilities and prognostic factors by Kaplan–Meier method. Results Age of diagnosis ranged from 3 months to 18 years (median age 16 years). The male to female ratio was 0.8 (202 male, 240 female). Most melanoma were located at the trunk (n = 195) and the lower extremity (n = 114). Patients with >3 months of follow-up (median 55 months) showed an overall survival (OS) of 94.8% in 5 years. Survival according to tumour stage was 98.5% for stage I (n = 190), 91.1% for stage II (n = 39) and 53.0% for stage III/IV tumours (n = 11). Worse outcome was seen in patients with nodular melanoma (OS 77.9%, n = 42) compared to superficial spread histotype (OS 100%, n = 138) or other histotype (OS 96.9%, n = 88) (p < 0.0001), in case of thicker tumours (Clark level IV or V, OS 87.1%, n = 84) compared to thinner tumours (Clark level I, II, III, OS 99.1%, n = 164) (p = 0.0008) and in case of ulceration (OS 65.6%, n = 17) compared to no ulceration (OS 99.2%, n = 182). Conclusion Patient and tumour characteristics in paediatric melanoma patients show no evident differences to adult melanoma cases. The same clinical approach as in adults should be used.